STRATEGI MARKETING “KRUPUK PATI” SEBAGAI SENTRA BISNISKHAS DUSUN MIRU DESA BANYUURIP - Imma Zaky Fuadah; Tri Utami; Awalia Ramadini; Nurindah Aprilina; Dandin Setia Rahayu; Abdullah Jabbar; Georgius Fantura (Kanigara, 2023)
The development of Home Industry is carried out as a support for improving the welfare of the community. The development of small industries will help to overcome the problem of unemployment. The development of an increasingly advanced era, especially in the era that is starting to enter 5.0, namely a society that can solve various challenges and social problems by utilizing various innovations born in the era of the industrial revolution 4.0. Banyuurip Village has a small starch cracker business produced by the mothers of the residents of Miru Hamlet. The marketing process that runs traditionally with on-site orders and orders through WhatsApp alone has an impact on the lack of widespread marketing of starch crackers. The program of building the signpost of the Pati Cracker center has been implemented smoothly and well. The program received a warm welcome from the Village Head, Hamlet Head and the community. It is recommended that more develop and run programs to develop and advance Banyuurip Village.